A simplified deformation forewarning method for longitudinal structural performance of existing shield tunnels based on Fast Fourier Transform. (January 2023) - Fu, Yanbin; Wang, Fudao; Hong, Chengyu; Wen, Junsheng; Zeng, Deqi
Graphical abstract: Highlights: A forewarning method for longitudinal structure performance of shield tunnel. Precise fitting function of measured data replaces Timoshenko displacement solution. Fast Fourier Transform is used to reconstruct the tunnel settlement data precisely. Deformation indexes are ranked based on the sensitivity of forewarning. Abstract: The longitudinal differential settlement of tunnel is the key factor to determine the safety of tunnel structure during service life. Based on the measured settlement data of the tunnel, this paper provides a forewarning method for defects locations. Firstly, Timoshenko beam is used to simulate the longitudinal mechanical response of the tunnel structure under the surrounding rock load, and the precise tunnel settlement curve reconstructed by Fast Fourier Transform (FFT) is used to replace the Timoshenko theoretical solution which is difficult to be solved directly. Combined with the tunnel longitudinal deformation forewarning analysis model, the approximate conversion between the longitudinal deformation curvature radius, circumferential joint opening, differential settlement and dislocation is carried out. The sensitivity of the deformation indexes is discussed through the dichotomy method. It is concluded that longitudinal deformation curvature radius is the most sensitive deformation indexes for the longitudinal structural performance of the tunnel. Finally, the forewarning results are compared with the actual diseases locations. The results show that the method can better determine the defect location of longitudinal tunnel structure in operation. The method can provide a better reference for deformation forewarning and performance evaluation of existing tunnel.